The generalization of some results for Schurer and Schurer-Stancu operators - Miclăuş, Dan (Rev. Anal. Numér. Théor. Approx., 2011)
In the present paper we generalize some results for Schurer and Schurer-Stancu operators. Firstly, we establish a general formula concerning calculation of test functions by Schurer operators. Secondly, using this relationship and some known results we prove in every case a Voronovskaja type theorem, the uniform convergence and the order of approximation for Schurer and Schurer-Stancu operators.